2006
DOI: 10.1136/ard.2005.049486
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal atrophy in systemic lupus erythematosus

Abstract: Objectives: To determine the frequency and progression of hippocampal atrophy in systemic lupus erythematosus (SLE) and the clinical, laboratory and treatment features associated with its occurrence. Methods: 150 patients with SLE and 40 healthy volunteers were enrolled in our study. A complete clinical, laboratory and neurological evaluation was performed. Magnetic resonance imaging was carried out using a 2T scanner (Elscint Prestige) and coronal T1-weighted images were used for manual volumetric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 38 publications
7
109
2
3
Order By: Relevance
“…Cortical and subcortical involvement seems to be driven by different factors, and even the rate of progression has been shown to be different in white and gray matter [9]. The impact of regional cerebral atrophy has also been studied, indicating that cognitive impairment may be present more frequently in both corpus callosum and hippocampal atrophy [9,18]. Mild or clinically insignificant spinal cord pathology has also been described in SLE, which might be secondary to Wallerian degeneration of long tract fibers passing through damaged areas of the brain [19].…”
Section: Conventional Mri Methodsmentioning
confidence: 98%
“…Cortical and subcortical involvement seems to be driven by different factors, and even the rate of progression has been shown to be different in white and gray matter [9]. The impact of regional cerebral atrophy has also been studied, indicating that cognitive impairment may be present more frequently in both corpus callosum and hippocampal atrophy [9,18]. Mild or clinically insignificant spinal cord pathology has also been described in SLE, which might be secondary to Wallerian degeneration of long tract fibers passing through damaged areas of the brain [19].…”
Section: Conventional Mri Methodsmentioning
confidence: 98%
“…The hippocampus, located in the temporal lobe, is a structure intimately associated with olfaction Several studies have shown that patients with SLE had significant hippocampal atrophy that correlated with disease duration, total corticosteroid dose and greater number of CNS manifestations [62]. In another study we have demonstrated that injection of anti-P ribosomal antibodies (anti-P) directly to the brain ventricles of mice induced depressive manifestations.…”
Section: Discussionmentioning
confidence: 96%
“…Selective involvement of the amygdala in patients with SLE and anti-NMDAR antibodies has been found . Cognitive impairment may be present more frequently in both corpus callosum and hippocampal atrophy (Appenzeller et al, 2006(Appenzeller et al, , 2008. Mild or clinically insignificant spinal cord pathology has also been described in SLE, which might be secondary to Wallerian degeneration of long tract fibers passing through damaged areas of the brain (Benedetti et al, 2007).…”
Section: Conventional Mrimentioning
confidence: 99%